P01.044 Impact of the addition of vinorelbine to temozolomide in the first-line treatment of pediatric high grade gliomas. (19th September 2018) - Guidi, M; Lucchesi, M; Buccoliero, A; Scoccianti, S; Farina, S; Fonte, C; Caporalini, C; Moscheo, C; Genitori, L; Sardi, I
Abstract: Background: Pediatric high-grade gliomas (HGGs) are comprised primarily of anaplastic astrocytomas (AA, WHO-grade III) and glioblastomas (GBM, WHO-grade IV). Despite advances in treatment for other childhood tumors, their outcomes are comparable to adults, with 5-year survival rates less than 20%. Primary treatment includes surgery, followed by radiotherapy and chemotherapy with temozolomide. Consolidated studies demonstrated that adjuvant treatment remains important for improving outcome. Material and Methods: We considered 19 HGG patients admitted to the Neuro-Oncology Unit in Florence between September 2008 and January 2018. Patients were enrolled in a temozolomide-vinorelbine chemotherapy protocol developed on the basis of EORTC-COG experiences. The children were subjected to resection and to radiotherapy with concomitant chemotherapy (6 weeks) with vinorelbine (20 mg/sqm i.v weekly), temozolomide (75 mg/sqm i.o daily). The adjuvant phase consisted in 12 months of treatment with exclusive chemotherapy with vinorelbine 30 mg/sqm i.v. days 1, 14 every 28, temozolomide 150 mg/sqm i.o. days 1–5 every 28. Results: The median age of 19 treated patients was 10 years (range 6–25). Six patients (31, 6%) had GBM and thirteen patients (68, 4%) had an AA. According the localization, 16 tumors (84, 2%) were sovratentorial and 3 (15, 8%) infratentorial tumors. Radical surgery was performed in seven patients. The median of follow-up was 50 months. At time of analysis, 12 patients were still alive and more than 50% of the patients have not yet relapsed. Five patients (26, 3%) had a disease progression during the adjuvant phase. One patient died after radiotherapy. The patients who received the highest dose of radiotherapy (59–60 Gy vs 54 Gy) showed better survival (not reached vs 38, 8 months). Patients who experienced disease progression during the maintenance treatment had a significant worst survival (11, 3 months vs NR p< 0.0001). Conclusion: Adjuvant chemotherapy is crucial for a better outcome of malignant gliomas. In pediatric HGGs, the combination of vinorelbine to temozolomide seems to be safely, without significant adverse events. At 50 months of follow-up (beyond the median OS described in the literature) more than 50% of patients have not yet experienced recurrence. Our analysis confirms that disease progression during the treatment represents a negative prognostic factor for survival. This may identify a subgroup of patients with a marked chemoresistance.